Suicidal Risk in People with Obsessive Compulsive Disorder - Wardha Novia Annisa; Athalita Andhera Nabil; I Komang Gede Andhika Wibisana; Sima Smith; Emmy Amalia (Jurnal Biologi Tropis, 2023)
Obsessive compulsive disorder or Obsessive Compulsive Disorder (OCD) is a psychiatric disorder characterized by excessive anxiety, persistent thoughts (obsessions), and repetitive behaviors (compulsions). The prevalence of OCD in Europe ranges from 0.1-2.3% annually and more common in adults. The risk of suicide increases ten times more in OCD sufferers compared to the non-OCD sufferers with prevalence the OCD sufferers who has thoughts of suicide is 23.3%. This literature review aims to determine the risk factors for suicide in OCD patients so that prevention can be carried out in individuals who have risk factors. In this literature review we conducted a search on the PubMed,  Google Schoolar, and Researchgate database  using  the search keyword “Obsessive Compulsive Disorder”, “Obsessive Compulsive Symptoms”, “Suicide”, “Self-murder”, and “Risk Factor”. OCD is a disease with genetic and non-genetic risk factors, can manifest clinically as obsessions and compulsions that occur due to failure in responding to yedasantience signals so that the security motivation system (SMS) will be activated longer than normal. The longer SMS activated, the more depressive symptoms can develop, which tends to give rise to suicidal thoughts. In conclusion, risk factors for suicide in OCD that can be identified earlier will not only help the patient's prognosis but also help them choose treatment steps that are appropriate with the severity of the OCD symptoms.